2010
DOI: 10.1038/ngeo1017
|View full text |Cite
|
Sign up to set email alerts
|

Miocene drainage reversal of the Amazon River driven by plate–mantle interaction

Abstract: Northern South America experienced significant changes in drainage patterns during the opening of the South Atlantic Ocean. Disappearance of a mega-wetland in the western Amazonian basins was followed by the formation of the eastward-draining Amazon River, which has been attributed to Andean uplift [1][2][3][4][5] . However, South America's westward motion over cold, dense subducted slabs implies that regional subsidence and uplift east of the Andes may have been driven by mantle convection. Here we use a coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
126
2
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(141 citation statements)
references
References 26 publications
(46 reference statements)
4
126
2
9
Order By: Relevance
“…This uplifted area is the site of numerous Neogene bauxitic and no-bauxitic plateaus, higher in the basin flanks and lower close to the central basin axis area. Large plateau tops reached about 250 m above sea level, according to SRTM 90 m digital elevation model (DEM) from NASA, as opposed to the conclusions of Shephard et al (2010), who stated subsidence lowered central and eastern basins of northern South America driven by mantle convection, from 14 Myr ago to date. Sacek (2014) concluded that the reversal of the Amazon River can be interpreted by the dynamics of surface processes and the flexure of the lithosphere in response to the formation of the Andes instead of regional uplift guided by mantle convection as proposed by Shephard et al (2010), but Sacek's (2014) hypothesis also fails to fully reproduce the area stratigraphic development.…”
Section: Purus Arch and Amazon Basinmentioning
confidence: 87%
See 1 more Smart Citation
“…This uplifted area is the site of numerous Neogene bauxitic and no-bauxitic plateaus, higher in the basin flanks and lower close to the central basin axis area. Large plateau tops reached about 250 m above sea level, according to SRTM 90 m digital elevation model (DEM) from NASA, as opposed to the conclusions of Shephard et al (2010), who stated subsidence lowered central and eastern basins of northern South America driven by mantle convection, from 14 Myr ago to date. Sacek (2014) concluded that the reversal of the Amazon River can be interpreted by the dynamics of surface processes and the flexure of the lithosphere in response to the formation of the Andes instead of regional uplift guided by mantle convection as proposed by Shephard et al (2010), but Sacek's (2014) hypothesis also fails to fully reproduce the area stratigraphic development.…”
Section: Purus Arch and Amazon Basinmentioning
confidence: 87%
“…Castro et al (1978 andShephard et al (2010) suggested it to have taken place in the Middle Miocene time; Hoorn et al (1995) and Figueiredo et al (2009) in the Late Miocene; Espurt et al (2007) and Roddaz et al (2005) not before the Pliocene; Latrubesse et al (2010), Campbell et al (2006) and Campbell (2010) in the Late Pliocene; and Almeida (1974) in the PlioceneEarly Pleistocene. Bezerra (2003), Rossetti et al (2005) and Bezerra and Ribeiro (2015) inferred the Amazon River to have flowed through the Tacutu Rift, the Essequibo River and the coast of Guyana Republic to the Atlantic Ocean in the Plio-Pleistocene and at the end of the Pleistocene and in the Holocene, being guided to its present valley site, by following neotectonic faults.…”
Section: Purus Arch and Amazon Basinmentioning
confidence: 99%
“…1 ISTerre Université de Grenoble 1, CNRS-IRD, F-38041 Grenoble, France. perturbation to oceanic circulation [Poore and White, 2011], large scale continental drainage reorganizations [Shephard et al, 2010] or the formation of major geomorphic features such as the Grand Canyon [Karlstrom et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…A principal mudança ao longo do desenvolvimento do sistema amazônico ocorreu no Mesomioceno-Neomioceno, com a inversão da direção de fluxo do sistema fluvial, que passou a drenar para o Oceano Atlântico (Hoorn et al, 1995(Hoorn et al, , 2010Shephard et al, 2010). Esse evento pode ser sustentado pela origem da foz do Rio Amazonas no Oceano Atlântico no período entre 11.8 e 8.3 Ma (Figueiredo et al, 2009;Gorini et al, 2014).…”
Section: Introductionunclassified
“…As idades atribuídas para Formação Solimões variam entre Mioceno e início do Plioceno (Hoorn, 1993;Leite, 2006;Leite et al, 2016;Silva-Caminha et al, 2010) O ambiente de deposição da Formação Solimões é predominantemente lacustre e fluvial, com episódios de incursões marinhas registrados por alguns autores no Mioceno inferior e médio/superior (Maia et al, 1977;Hoorn, 1993;Hoorn et al, 1995Hoorn et al, , 2010Cozzuol, 2006;Lovejoy et al, 2006;Latrubesse et al, 2007Latrubesse et al, , 2010Silva-Caminha et al, 2010;Shephard et al, 2010;Linhares et al, 2011;Boonstra et al, 2015).…”
Section: Introductionunclassified